Proceedings of the ACM 2012 Conference on Computer Supported Cooperative Work 2012
DOI: 10.1145/2145204.2145219
|View full text |Cite
|
Sign up to set email alerts
|

How and to whom people share

Abstract: The global expansion of the use of online communities, including social networking sites, necessitates a better understanding of how people self-disclose online, particularly in different cultures. In a scenario-based study of 1,064 respondents from the United States and China, we aimed to understand how self-disclosure is affected by communication mode (face-to-face vs. online), type of relationship and national culture. Our findings show that national culture interacts with communication mode and type of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…For example, North Americans tend to disclose more than Chinese (Chen, 1995), Japanese (Schug, Yuki, &Maddux, 2010), or East Europeans (Maier, Zhang, & Clark, 2013) under face-to-face conditions. However, in computer-mediated environments self-disclosure increases for Asians, which has been attributed to the fact that members of collectivistic cultures are more reserved in face-to-face interactions to avoid violating social norms (Zhao, Hinds, & Gao, 2012). Descriptive results could not corroborate these results in the current meta-analysis (see Table 5) because few effects were available from outside the United States.…”
Section: Limitations and Outlookmentioning
confidence: 71%
“…For example, North Americans tend to disclose more than Chinese (Chen, 1995), Japanese (Schug, Yuki, &Maddux, 2010), or East Europeans (Maier, Zhang, & Clark, 2013) under face-to-face conditions. However, in computer-mediated environments self-disclosure increases for Asians, which has been attributed to the fact that members of collectivistic cultures are more reserved in face-to-face interactions to avoid violating social norms (Zhao, Hinds, & Gao, 2012). Descriptive results could not corroborate these results in the current meta-analysis (see Table 5) because few effects were available from outside the United States.…”
Section: Limitations and Outlookmentioning
confidence: 71%
“…Cross-cultural studies in the area of computer security and privacy studied the differences in privacy concerns and behavior between different cultures and explored the reasons underlying these differences (e.g., [2,3,12,32,53,57]). For example, Almakrami compared the self-disclosure practices of Saudis on Facebook with those of Australians [2].…”
Section: Culture In Computer Security and Privacymentioning
confidence: 99%
“…Various research efforts compared the privacy (but not security) concerns of Internet users from Asian countries with those of their counterparts from western countries [27,29,34,35,53,52,57]. In general, most of these efforts concluded that the Asian users are less concerned about their online privacy than users from western countries.…”
Section: Culture In Computer Security and Privacymentioning
confidence: 99%
“…Haddad et al compare two different interface designs among older adult Caucasians and East Asians and find preference differences in interface design [22]. Social media usage has also been investigated cross-culturally, highlighting differences in self-presentation [53], self-disclosure [52], as well as tasks such as brainstorming [47]. These studies have typically contrasted American and Chinese user populations.…”
Section: Related Workmentioning
confidence: 99%